Relationship Between the Nasopharyngeal Swab Sampling Method, Nasal Obstruction, and SARS-Cov-2 Positivity - Dogan Cakan; Zeliha Kubra Cakan; Semih Usaklioglu; Yetkin Zeki Yilmaz; Omer Uysal; Hasan Ahmet Ozdogan (Haseki Tıp Bülteni)

(untitled)
Aim:We think that the nasopharyngeal swab sample should be taken bilaterally to improve the sensitivity of the real-time-reverse transcriptase-polymerase chain reaction (RT-PCR) test since there may be pathologies that cause nasal obstruction, such as nasal septum deviation (NSD). In this context, we investigated the effect of the nasopharyngeal swab sampling method and the presence of nasal obstruction on the detection of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2).Methods:This prospective clinical study was conducted from March 2021 to January 2022. Forty-four hospitalized patients with NSD were included in the study group, and 44 hospitalized patients without NSD were included in the control group. The results of the RT-PCR test studied with a unilateral nasopharyngeal swab sample taken during hospitalization and the RT-PCR test studied with a bilateral nasopharyngeal swab sample taken on the 2nd day of hospitalization and the visual analog scale (VAS) scores showing the patients’ pain during the first sampling were determined.Results:In the first test, 23 (52.3%) patients in the study group and 32 (72.7%) patients in the control group were evaluated as SARS-CoV-2 positive. The first test sensitivity was significantly higher in the control group (p=0.048). The VAS score was significantly higher in the study group (p=0.00008). In the second test, 35 (79.5%) patients in the study group and 37 (84.1%) patients in the control group were evaluated as SARS-CoV-2 positive. The sensitivity increases in the study group and in the population were statistically significant (p=0.007 and p=0.004, respectively). The consistency of the first and second test results increased in patients without NSD and in patients with low VAS scores [odds ratio (OR)=3.779; p=0.001, OR=2.572; p=0.005, respectively].Conclusion:Nasopharyngeal swab sampling may be affected by nasal congestion and the sampling method. To avoid this, it may be more appropriate to take a nasopharyngeal swab sample through the bilateral nasal cavity.